Use of the 6-methylsalicylic-acid-synthase gene as a discriminating marker between Aspergillus terreus and Aspergillus flavipes - Pazoutová, S; Hamplová, I; Anderson, M; Denning, D W (Folia microbiologica, 1999)
In nineteen pathogenic and saprophytic isolates denoted as Aspergillus terreus the presence and restriction pattern of the gene pksM (6-methylsalicylic acid synthase) was determined. Five patterns (A-E) were found and in three isolates the gene was missing. The RAPD (Random Amplified Polymorphic DNA) patterns with three primers were analyzed. The strains with pksM pattern possibly derived from the most common pattern A by single mutation (patterns B-D) were also related by RAPD. Among them, three clades were found. The first one contained saprophytes from Asia, the other two clades contained both European and American pathogens and each of them one saprophyte. The sequences of rDNA region containing 5.8S rDNA and spacers ITS1 and ITS2 were established for representatives of each group and the strains missing the pksM gene. The isolates possessing pksM (although with different restriction patterns) grouped as A. terreus group, whereas the isolates lacking this gene were close to Fennellia flavipes.
Keywords: Random Amplified Polymorphic DNA Technique; geny hub; technika náhodné amplifikace polymorfní DNA; DNA, Fungal; Oxidoreductases; polymorfismus genetický; fylogeneze; RNA ribozomální 5.8S; restrikční mapování; Aspergillus; ligasy; Phylogeny; Restriction Mapping; acyltransferasy; Sequence Analysis, DNA; Ligases; ribozomální DNA; sekvenční analýza DNA; Aspergillosis; oxidoreduktasy; aspergilóza; Polymorphism, Genetic; Multienzyme Complexes; DNA fungální; Genes, Fungal; Acyltransferases; lidé; Humans; multienzymové komplexy; DNA, Ribosomal; RNA, Ribosomal, 5.8S